2019
DOI: 10.1016/j.cell.2019.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Independence of the Liver Circadian Clock

Abstract: SUMMARY Mammals rely on a network of circadian clocks to control daily systemic metabolism and physiology. The central pacemaker in the suprachiasmatic nucleus (SCN) is considered hierarchically dominant over peripheral clocks, whose degree of independence, or tissue level autonomy, has never been ascertained in vivo. Using arrhythmic Bmal1-null mice, we generated animals with reconstituted circadian expression of BMAL1 exclusively in the liver (Liver-RE). High-throughput transcriptomics and metabolomics show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

22
279
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 247 publications
(302 citation statements)
references
References 83 publications
(94 reference statements)
22
279
1
Order By: Relevance
“…A previous study has demonstrated that expression levels of clock genes including PER1 and PER2 differ before and after feeding as well as in different tissues, such as the hypothalamus, the skeletal muscle, and the liver, in swine . Koronowski et al have generated transgenic mice, which have a stop cassette inserted between exon 5 and 6 of BMAL1 resulting in global BMAL1 knockout phenotypes . The stop cassette was flanked by loxP sites and crossing those global BMAL1 −/− mice with mice that express Cre recombinase under the control of α‐fetoprotein enhancer ( Alfp ‐Cre mice) allowed the removal of the stop cassette specifically in Alfp‐positive hepatic cells .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…A previous study has demonstrated that expression levels of clock genes including PER1 and PER2 differ before and after feeding as well as in different tissues, such as the hypothalamus, the skeletal muscle, and the liver, in swine . Koronowski et al have generated transgenic mice, which have a stop cassette inserted between exon 5 and 6 of BMAL1 resulting in global BMAL1 knockout phenotypes . The stop cassette was flanked by loxP sites and crossing those global BMAL1 −/− mice with mice that express Cre recombinase under the control of α‐fetoprotein enhancer ( Alfp ‐Cre mice) allowed the removal of the stop cassette specifically in Alfp‐positive hepatic cells .…”
Section: Introductionmentioning
confidence: 99%
“…Cre expression is observed selectively in hepatocytes and cholangiocytes in Alfp ‐Cre mice . As a result, crossed mice expressed BMAL1 only in the liver (hepatocytes and cholangiocytes) . Global BMAL1 −/− mice lost circadian rhythms and expressions, but mice with hepatic BMAL1 expression had rhythmic circadian expressions and metabolisms in the liver without BMAL1 expression and circadian rhythms in the brain and other organs .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations